Taking higher order thinking seriously: Using Marzano's taxonomy in the economics classroom. (January 2016) - Dubas, Justin M.; Toledo, Santiago A.
Abstract: This paper argues for the need for instructors to more intentionally foster higher order thinking skills in economics students, as these skills lend themselves to longer-lasting, more transferable knowledge. This paper proposes the use of Marzano's taxonomy to aid in this endeavor. It provides a clear functional delineation between lower- and higher-order thinking, and serves as a natural way to systematically build a course around incrementally building up student thinking skills. We outline how it was used in course design for drafting student learning outcomes (SLOs), creating assessments for a Principles of Economics course, and leveraging it as a tool to provide more targeted feedback for students. Preliminary observations on the impact on student learning are presented.